PERANCANGAN INFOGRAFIS PENCEGAHAN OSTEOPOROSIS SEJAK DINI DALAM MEDIA MOTION GRAPHIC - WIZA MIARTI, Dr. M. Nasrul Kamal, M.Sn., Dini Faisal, S.Ds., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
The Motion Graphic Media are designed to persuade the society to care more about the health of Bones. The expected audience for the media is those who are around 15 to 35 years old. By showing them about the causes and prevention efforts of Osteoporosis, it is hoped that they will start to take care of the health of their Bones.The method of designing the ladjamudin 2005 motion graphic, the design has the purpose of designing a new system. The stages in this design are fiber data collection data analysis. They are collecting the data, analysing them, and finally designing the media. Data were obtained from observation and interview with an orthopaedist. Later, they were analysed by using 5W + 1H. This design will be delivered in the main media in the form of motion graphics, and X-banner, posters, notebooks, CD covers, pins, towels and stickers as supporting media.Keywords: Osteoporosis, the Motion Graphic, Media